Symptoms compatible with functional bowel disorders are common in patients with quiescent ulcerative colitis and influence the quality of life but not the course of the disease - Georgios Mavroudis; Magnus Simren; Börje Jonefjäll; Lena Öhman; Hans Strid (Therapeutic Advances in Gastroenterology, 2019)
Background: Whether patients with inactive ulcerative colitis (UC) have symptoms compatible with functional bowel disorders (FBDs) other than irritable bowel syndrome (IBS) is unclear. Our aim was to investigate the prevalence and burden of these symptoms and determine impact on the UC course. Methods: We used Mayo score, sigmoidoscopy and calprotectin (f-cal) to define remission in 293 UC patients. Presence of symptoms compatible with FBD, severity of gastrointestinal, extraintestinal and psychological symptoms, stress levels and quality of life (QoL) were measured with validated questionnaires. At 1 year later, remission was determined by modified Mayo score and f-cal in 171 of these patients. They completed the same questionnaires again. Results: A total of 18% of remission patients had symptoms compatible with FBD other than IBS, and 45% subthreshold symptoms compatible with FBD. The total burden of gastrointestinal symptoms in patients with symptoms compatible with FBD was higher than in patients without FBD ( p < 0.001), which had negative impact on QoL ( p = 0.02). These symptoms were not correlated with psychological distress, systemic immune activity or subclinical colonic inflammation and were not a risk factor for UC relapse during follow up. Conclusion: Symptoms compatible with FBD other than IBS are common during UC remission influencing patients’ QoL but not the UC course.